OPTIMALISASI PENGETAHUAN MELALUI EDUKASI PENYAKIT HIPERTENSI DI DESA SEPABATU - Haerianti, Masyita; Irwan, Muhammad; Wabula, Irfan; Rahmi Latif, Auliah (GEMASSIKA: Jurnal Pengabdian Kepada Masyarakat, 2025)
Hypertension is one of the most common non-infectious diseases throughout the world with a prevalence that continues to increase every year. Hypertension will cause various complications such as stroke, kidney failure, cardiac hypertrophy, myocardial infarction and heart failure. One of the possible ways to treat the complications of hypertension by providing education. This activity aims to increase public knowledge about hypertension. This activity was carried out through a method of health education using power point presentations and leaflets to 21 people in the Sepabatu village community. Optimizing knowledge through education was assessed by administering a questionnaire which was measured twice, namely a pre-test before education and a post-test after education was provided, combined with the provision of leaflets. Not only does knowledge measure, but people also check their blood pressure. The results of activities show an increase in knowledge before education (60.48) increasing to (70.95) after post-test. Health education is one of the tools that can be used to provide knowledge to the public regarding hypertension so that people can adopt a healthy lifestyle to prevent hypertension or take actions that can be taken to treat hypertension.